Pengaruh Harga Inovasi Produk Dan Promosi Melalui Media Online Instagram Terhadap Keputusan Pembelian (Survey Pada Konsumen Di Toko Handmade Shoes Surabaya) - Agustin, Alfianti; Maduwinarti, Ayun; Mulyati, Awin (Universitas 17 Agustus 1945 Surabaya, 2021)
ABSTRACT The company must determine the marketing strategy used to compete. The marketing strategy applies the target market and marketing mix or better known as 4P (product, place, price and promotion). Companies are competing to dominate market share. By having a unique product, consumers will be interested, in this way the company will dominate the market. The purpose of this study was to determine the effect of Price, Product Innovation and Promotion on Consumer Purchasing Decisions in Surabaya Handmade Shoes Stores. As for supporting this research, the authors use quantitative methods with survey research using questionnaires as instruments. The population in this study were consumers who bought bags and shoes at the Handmade Shoes Store in Surabaya. The sample of this study used a non-probability sampling method (non-random sampling) with a purposive sampling technique of 100 respondents. The data analysis technique used is multiple regression analysis. The results of this study indicate that all independent variables namely Price, Product Innovation and Promotion through Instagram Online Media have a positive influence on the dependent variable namely the Purchasing Decision.Keywords: Price, Product Innovation, Promotion and Purchasing Decisions.